A microwave assisted one-pot route synthesis of bimetallic PtPd alloy cubic nanocomposites and their catalytic reduction for 4-nitrophenol. (16th October 2017) - Zhang, Jian; Gan, Wei; Fu, Xucheng; Hao, Hequn
Abstract: We herein report a simple, rapid, and eco-friendly chemical route to the one-pot synthesis of bimetallic PtPd alloy cubic nanocomposites under microwave irradiation. During this process, water was employed as an environmentally benign solvent, while dimethylformamide served as a mild reducing agent, and polyvinylpyrrolidone was used as both a dispersant and a stabilizer. The structure, morphology, and composition of the resulting alloy nanocomposites were examined by x-ray diffraction, transmission electron microscopy, and energy dispersive x-ray spectroscopy. A detailed study was then carried out into the catalytic activity of the PtPd nanocomposites with a Pt:Pd molar ratio of 50:50 in the reduction of 4-nitrophenol (4-NP) by sodium borohydride as a model reaction. Compared with pristine Pt and Pd monometallic nanoparticles (PtNPs and PdNPs), the bimetallic PtPd alloy nanocomposites exhibited enhanced catalytic activities and were readily recyclable in the reduction of 4-NP due to synergistic effects.